2001
DOI: 10.1016/s0735-1097(00)01185-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an endothelial-type nitric oxide synthase isoform in human neutrophils: modification by tumor necrosis factor-alpha and during acute myocardial infarction

Abstract: These observations demonstrate that human neutrophils express eNOS, which is downregulated by TNF-alpha and during AMI. This effect is associated with increased binding of neutrophil cytosolic proteins to the 3'-UTR of eNOS mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…eNOS is also expressed in both mouse and human neutrophils, monocytes, and macrophages, as well as in human immature myeloid cells (81)(82)(83)(84)(85)(86)(87). In the mouse model, on the other A proposed model for signaling mechanisms of MDL-1-mediated shock.…”
Section: Figurementioning
confidence: 99%
“…eNOS is also expressed in both mouse and human neutrophils, monocytes, and macrophages, as well as in human immature myeloid cells (81)(82)(83)(84)(85)(86)(87). In the mouse model, on the other A proposed model for signaling mechanisms of MDL-1-mediated shock.…”
Section: Figurementioning
confidence: 99%
“…However, presence of both nNOS and iNOS has been accepted unequivocally (23)(24)(25), whereas occurrence of eNOS in human neutrophils (26), is still being advocated. Rodents are commonly exploited for the various NO-mediated investigations.…”
mentioning
confidence: 99%
“…In vitro studies have shown that inflammation, and more particularly cytokines are intimately involved in the downregulation of eNOS protein in both the endothelium and leukocytes. 19,20 In this regard, a recent review from Jeremy et al 21 and Giugliano et al 22 have suggested a relationship between ED and inflammation. The expression of eNOS protein seem to be preserved in the mononuclear cells from the patients with ED of neurological origin, which could be related to a lower production of inflammatory mediators than in the patients with ED of vascular origin.…”
Section: Discussionmentioning
confidence: 99%